2021
DOI: 10.3389/fmech.2021.671457
|View full text |Cite
|
Sign up to set email alerts
|

XANES Study of Tribofilm Formation With Low Phosphorus Additive Mixtures of Phosphonium Ionic Liquid and Borate Ester

Abstract: The development of low phosphorus engine oils is important to minimize phosphorus-induced exhaust catalyst poisoning and resulting in harmful emissions. In this study, low phosphorus oil formulations were prepared by using an ashless additive mixture of borate ester (SB) with ionic liquid composed of a phosphonium cation and phosphate anion (P_DEHP) at 350 and 700 ppm phosphorus. Tribological properties of this binary additive system were evaluated using a reciprocating cylinder on a flat test configuration. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 80 publications
(102 reference statements)
0
1
0
Order By: Relevance
“…Similar studies aiming to develop extreme pressure (EP), antiwear (AW), and FM additives that are empowered by fuel contamination and work well in lubricants formulated with higher levels of detergents and dispersants are of the utmost importance to increase engine reliability and efficiency. For example, because products of the antiwear additive (AW) ZDDP compromise the efficiency of the catalytic converter in the exhaust system, environmental pressures have led to a rush for alternative AW additives that produce lower levels of sulphur and phosphorous emissions [63]. The interaction of alternative AW additives and ethanol should be urgently investigated in order to determine whether they can better protect surfaces in ethanol-fuelled engines while reducing damage to the exhaust system.…”
Section: Knowledge Gaps Future Trends and Lubricant Guidelinesmentioning
confidence: 99%
“…Similar studies aiming to develop extreme pressure (EP), antiwear (AW), and FM additives that are empowered by fuel contamination and work well in lubricants formulated with higher levels of detergents and dispersants are of the utmost importance to increase engine reliability and efficiency. For example, because products of the antiwear additive (AW) ZDDP compromise the efficiency of the catalytic converter in the exhaust system, environmental pressures have led to a rush for alternative AW additives that produce lower levels of sulphur and phosphorous emissions [63]. The interaction of alternative AW additives and ethanol should be urgently investigated in order to determine whether they can better protect surfaces in ethanol-fuelled engines while reducing damage to the exhaust system.…”
Section: Knowledge Gaps Future Trends and Lubricant Guidelinesmentioning
confidence: 99%
“…As a result, molybdenum dialkyl dithiocarbamate (MoDTC) was introduced as another promising additive that can form a low-friction tribofilm [ 4 , 13 ] possessing a lattice structure consisting of MoS 2 nanosheets, although it has been reported that MoS 2 tribofilms are much easier to remove than ZDDP tribofilms [ 18 ]. Effective low-friction/antiwear tribofilms have also been produced from phosphorous- and sulfur-containing ionic liquids [ 4 , 19 , 20 , 21 ] and ceramic nanocrystals [ 22 ], through the synergy of transition metal oxide nanoparticles and conventional sulfur-containing oil additives [ 23 ], borate-modified blends [ 24 ], and borate-, phosphorous-, and sulfur-containing white oil and gear oil [ 25 , 26 , 27 ]. The good stiffness and strength, easy-to-shear ability, and potential to form antiwear tribofilms of two-dimensional transition metal carbides, nitrides, and carbonitrides, collectively known as MXenes, have also made them attractive additive candidates for tribological applications [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%